2010
DOI: 10.5539/ijbm.v5n10p137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis the Determinants of Market Stock Price Movements: An Empirical Study of Jordanian Commercial Banks

Abstract: Financial firms make up a substantial fraction of the domestic equity market. A number of studies subsequently used different conceptual and methodological approaches to model equity return of financial services firms. Movement of the stock price as the consequence of the movement of the micro and macroeconomic factors is strongly supported by the literature review. Amman Stock Exchange in Jordan is inefficient in weak form.The sample of study includes the 14 commercial banks of Amman Stock Exchange for the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 20 publications
2
28
0
1
Order By: Relevance
“…The other empirical studies viz. Taulbee (2005), Nawazish (2008), Al-Shubiri (2010), Sharma (2011), Khan and Amanullah (2012), Srinivasan (2012), Malhotra and Tandon (2013), Almumani (2014) among others reveal that various factors in different markets determine the share price. Determining share prices is a complex and conflicting task.…”
Section: Introductionmentioning
confidence: 99%
“…The other empirical studies viz. Taulbee (2005), Nawazish (2008), Al-Shubiri (2010), Sharma (2011), Khan and Amanullah (2012), Srinivasan (2012), Malhotra and Tandon (2013), Almumani (2014) among others reveal that various factors in different markets determine the share price. Determining share prices is a complex and conflicting task.…”
Section: Introductionmentioning
confidence: 99%
“…& Roulstone (2004) concluded that market prices of the stock depends on demand-supply forces of a particular security in the stock market . Several researchers also concluded that accounting reporting influenced the market value of corporate stock (Svensson & Larsson, 2009;AL-Shubiri, 2010;Sharma, 2011;Andriantomo & Yudianti , 2013 ;Bhatt & Sumangula, 2012 ;Halonen, Pavlovic and Persson , 2013). Besides accounting information, some macro and micro economic factors also affect market value of shares (AL-Shubiri , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers also concluded that accounting reporting influenced the market value of corporate stock (Svensson & Larsson, 2009;AL-Shubiri, 2010;Sharma, 2011;Andriantomo & Yudianti , 2013 ;Bhatt & Sumangula, 2012 ;Halonen, Pavlovic and Persson , 2013). Besides accounting information, some macro and micro economic factors also affect market value of shares (AL-Shubiri , 2010). Gross domestic products, interest rates, current account, and employment have an impact on stock prices movement (Kurihara, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing literature on the equity market show that the price efficiency of equity market has been examined by studying the relationships between the micro, macroeconomic factors and the equity share prices (Aug & Chiona, 2010;Shubiri, 2010;Nazir et al, 2010;Buyuksalvarci, 2010;and Pilinkus, 2010). Govindarajan et al, 2012 documented that Equity share price volatility is generally related with the internal and the external factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal factors can be classified as microeconomic factors that are related to the individual operation of the firms-capital expenditure, company management, insider trading, dividend policy, company share and value in the sector (Özlen & Ergun, 2012). The obtainable literature on the effect of microeconomic factors on equity prices such as Irfan and Nishat (2002), Low (2007), Shubiri (2010), Khan et al (2011), Irmala et al (2011), Ali (2011, Özlen and Ergun (2012), See & Jusoh (2012), and Shah et al (2012) showed that there are many internal variables that affect the companies or funds' performance in equity market which in turn impact the price level. For instances, dividend yield, dividend announcement, earning per share, management performance, risk's volatility, credibility, and size and capital growth of the firms or fund portfolios size.…”
Section: Literature Reviewmentioning
confidence: 99%